The Relationship Between Physical Activity and the Incidence of Diabetes Melitus - Nabila Putri, Zahra; Kusdiyah, Erny; William Gading, Patrick (LPPM Universitas Jambi, 2025)
Background: The highest prevalence of DM is at the Putri Ayu Community Health Center, Jambi City, with the highest number of DM sufferers who receive standard health services, namely 441 cases in 2022. The aim of this study is to determine the relationship between physical activity and the incidence of Diabetes Mellitus. Method: This study employed a quantitative research method with an analytical case–control study design. Population and Control Population in this study were all DM sufferers in the working area of ​​the Putri Ayu Community Health Center, Jambi City. the of samples in the case group was 90 respondents and the samples in the control group was 90 respondents. The total sample in this study was 180 respondents. Data collection techniques use questionnaires. Data analysis in this research is Univariate Analysis, and Bivariate Analysis uses Chi Square. Result: The largest proportion of gender in the case and control groups was found to be women at 31,1%, the majority of ages in the case and control groups were in the early elderly age group (46-55 years) at 20%, the type of work in the case group was found the type of work was 48 housewives (26,7%) and 40 controls (22,2%). The statistical test used was the Chi Square test, resulting in a p-value of 0.000 (p < 0.05) (OR 6.417). Conclusion: This study demonstrates that physical activity is an important factor associated with the incidence of diabetes mellitus in the working area of Putri Ayu Public Health Center, Jambi City, in 2024. Individuals with lower levels of physical activity were found to have a substantially higher risk of developing diabetes mellitus compared to those who engage in higher levels of physical activity. These findings highlight the importance of promoting regular physical activity as part of diabetes prevention and control efforts at the community level. Therefore, increasing regular physical activity in accordance with the recommendations of the American Diabetes Association should be emphasized as an effort to control and prevent diabetes mellitus.